A Highly Selective Potassium Sensor for the Detection of Potassium in Living Tissues. Issue 42 (25th August 2016) - Depauw, Alexis; Dossi, Elena; Kumar, Naresh; Fiorini‐Debuisschert, Céline; Huberfeld, Gilles; Ha‐Thi, Minh‐Huong; Rouach, Nathalie; Leray, Isabelle
Abstract: The development of highly selective sensors for potassium is of great interest in biology. Two new hydrosoluble potassium sensors (Calix‐COU‐Alkyne and Calix‐COU‐Am) based on a calix[4]arene bis(crown‐6) and an extended coumarin were synthesized and characterized. The photophysical properties and complexation studies of these compounds have been investigated and show high molar extinction coefficients and high fluorescence quantum yields. Upon complexation with potassium in the millimolar concentration range, an increase of one‐ and two‐photon fluorescence emission is detected. A twofold fluorescence enhancement is observed upon excitation at λ =405 nm. The ligands present excellent selectivity for potassium in the presence of various competitive cations in water and in a physiological medium. The photophysical properties are not affected by the presence of a large amount of competing cations (Na +, Ca 2+, Mg 2+, etc.). Ex vivo measurements on mouse hippocampal slices show that Calix‐COU‐Alkyne accumulates extracellularly and does not alter the neuronal activity. Furthermore, the sensor can be utilized to monitor slow extracellular K + increase induced by inhibition of K + entry into the cells. Abstract : Two new hydrosoluble potassium sensors (Calix‐COU‐Alkyne and Calix‐COU‐Am) based on a calix[4]arene bis(crown‐6) and an extended coumarin were synthesized and characterized. Ex vivo measurements on mouse hippocampal slices show that the Calix‐COU‐Alkyne accumulates extracellularly and does not alter the neuronal activity (see figure). It can also be utilized to monitor slow extracellular K + increase induced by inhibition of K + .